Mengenal Kota Solo Menggunakan Augmented Reality Berbasis Android - Syah, Baharudin; , Endah Sudarmilah, S.T., M.Eng (2015)
Solo City is a city of culture and history exist in Central Java, Solo has several historic sites that can be visited, namely keratin Kasunanan, market - traditional markets and quality batik. Augmented Reality is a technology that is growing. This technology can be used for media information, learning, and others. Therefore, the authors utilize this technology to memngembangkan apliksai for media information. By using this technology the authors made the media information to know the city of Solo. So as to give the information to the places that exist in the city of Solo. Application development Agumented Reality (AR) to know the city this solo through several stages, including needs analysis, data gathering, application design, application development, and testing of applications. And request the opinion of the public on this application. Based on the trial data, the conclusion that compelling applications and can help people find out information about the town solo but has not become one of the media information.